Contextualization of Classical Text Teaching in Traditional and Modern Pesantren - Rasyid, Hilman; Masruri, G. Ginanjar; Nugraha, Heru; Sarbini, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to analyze the contextualization of classical text teaching in both traditional and modern pesantren through a socio-cultural approach, focusing on adapting teaching methods and their relevance in addressing the changes of the times. A qualitative approach with descriptive-analytical methods was employed to investigate the contextualization of classical text instruction in modern pesantren (Pesantren Persis 67 Benda) and traditional pesantren (Pesantren Miftahul Huda) in Tasikmalaya. Data collection techniques included passive participant observation, structured interviews, and documentation studies, with data analysis based on the Miles and Huberman model conducted before, during, and after fieldwork. Triangulation, extended observations, and enhanced rigor were applied to ensure data credibility. The findings indicate that traditional pesantren maintain classical methods such as sorogan and bandongan, while modern pesantren adopt integrative approaches that combine Islamic traditions with technology-based and contemporary scientific learning methods. Both models successfully preserve the relevance of classical texts in shaping the character of students through strong spiritual and ethical values. In conclusion, the contextualization of classical text teaching in pesantren not only serves as a strategy to preserve the intellectual heritage of Islam but also as an educational paradigm that adapts to global challenges, ensuring that pesantren remains relevant as leading educational institutions in the modern era.